Global nlassical solvability of a problem with nonlocal conditions for degenerate hyperbolic system of the first order equations - R. V. Andrusyak; V. M. Kyrylych; O. V. Peliushkevych (Математичні Студії)
Using the method of characteristics and the Banach fixed point theorem we established the existence and uniqueness of a global classical (smooth) solution to an initial-boundary value problem with nonlocal boundary conditions for a hyperbolic integro-differential system involving equations without time derivative of unknown functions.